Diurnal temperature range variability driven by cloud cover and precipitation in Mongolian Plateau under global warming - Na, Li; Na, Risu; Bao, Yulong; Zhang, Jiquan; Bao, Yuhai; Shan, Yin (International journal of climatology, 2022)
The diurnal temperature range (DTR) has significantly decreased in many land areas as a consequence of global warming. The DTR spatial distribution and future projections of spatiotemporal variations in the case of global warming levels at 1.5 and 2.0°C under the RCP4.5 emission scenario was investigated using datasets from the Climatic Research Unit (CRU‐TS v.3.24.01) and the Coupled Model Intercomparison Project Phase 5 (CMIP5) in the Mongolian Plateau. And the main factors influencing DTR spatiotemporal variations were also evaluated using the Geo‐detector model at different time scales. The results showed that variations of the DTR significant decrease in snow‐winter dry‐warm summer climate region are higher than in other climate regions in spatial scale. As a result of the increasing rates of Tmin, which was more than double that of Tmax, the DTR decreased significantly on a temporal scale. In climate projections, the DTR was lower at global warming of 2.0°C (2037–2056) than 1.5°C (2017–2036). Precipitation was determined to be the predominant factor underlying the annual and seasonal (spring, summer, and autumn) DTR changes. Total cloud cover was the main factor in winter. Soil moisture was the key factor for the spatial variations in DTR in the warm and dry seasons. This study enhances the understanding of climate change in the Mongolian Plateau and provides a strong reference for other DTR variation studies in similar climates. The geographical location of the study area and spatial variation of the elevation and climate classifications.